Behta I. A. Area sales discourse character in focus readers’ perceptions - Behta I. A. (Philological Treatises, 2020)
The article is devoted to the analysis of the fictional text of the English post/modern period where the general principles of the textual structuring are manifested. They are necessary for the comprehension of the fictional text of the period of post/modern as speech and thought presentation in such texts is not considered the system of deviations from the language norm, but the system of gaining proficiency in a diverse communicatively-pragmatic and artistic potential of the language.